1997
DOI: 10.1002/(sici)1097-4679(199708)53:5<517::aid-jclp14>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Expanded norms for the controlled oral word association test

Abstract: The Controlled Oral Word Association Test (COWAT) is a measure of a person's ability to make verbal associations to specified letters (i.e., C, F, and L). This measure is a useful component of a neuropsychological battery as it is able to detect changes in word association fluency often found with various disorders. In order to generate current norms for the elderly and aid in interpreting their performance, the COWAT was administered to a group of community-dwelling elderly persons. Information regarding tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
(9 reference statements)
0
38
0
1
Order By: Relevance
“…Of those studies conducted in non-English speaking countries that administered tests including a language comprehension component, 51% did not report the use of measures that were validated in the native language. Consider, for example, verbal fluency tests, and particularly the Controlled Oral Word Association Test (COWAT), where participants are asked to produce as many words as possible starting with the letters F, A, and S (or C, F, L) within the time frame of 1 min (Sumerall et al, 1997). It has long been demonstrated that performance on phonemic verbal fluency tests fluctuates significantly as a function of the choice of letters representing different frequencies of words beginning with these letters in a given language (Borkowski et al, 1967).…”
Section: Validation Of Tests In Non-english Speaking Countriesmentioning
confidence: 99%
“…Of those studies conducted in non-English speaking countries that administered tests including a language comprehension component, 51% did not report the use of measures that were validated in the native language. Consider, for example, verbal fluency tests, and particularly the Controlled Oral Word Association Test (COWAT), where participants are asked to produce as many words as possible starting with the letters F, A, and S (or C, F, L) within the time frame of 1 min (Sumerall et al, 1997). It has long been demonstrated that performance on phonemic verbal fluency tests fluctuates significantly as a function of the choice of letters representing different frequencies of words beginning with these letters in a given language (Borkowski et al, 1967).…”
Section: Validation Of Tests In Non-english Speaking Countriesmentioning
confidence: 99%
“…The Controlled Oral Word Association Test (COWAT) requires individuals to produce as many words as possible in a one minute period that begin with a specified letter. 38,39 Standard administration with the letters F, A and S was used, along with the alternate version R, W and T. 34 The COWAT has demonstrated strong internal consistency and test-retest reliability with the use of alternate forms. 40 Attention and working memory.…”
Section: Cognitive Performance Measuresmentioning
confidence: 99%
“…Bonferroni-corrected pairwise comparisons carried out on the main effect of conditions showed that performance in the condition assessing STM for shape only and color only did not differ and both were better than performance in the condition assessing STM for shape-color binding (p \ 0.001 in both cases). [85]; letter fluency (FAS) [78]; verbal fluency (animals) [81]; TMT [80]; Rey Figure [21] In order to assess the interaction, post-hoc tests were carried out across groups for each condition separately. This showed that depressed patients and controls did not differ in any of the experimental conditions and both groups performed significantly better than AD patients only in the condition assessing STM for shape-color binding (p \ 0.001 in both cases).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%